El análisis de componentes principales identifica diferentes perfiles de rendimiento en función de las posiciones en partidos internacionales de hockey hierba femenino - Morencos, E.; Romero-Moraleda, B.; Rico-González, M.; Rojas-Valverde, D.; Pino-Ortega, J. (Revista Internacional de Ciencias del Deporte, 2021)
An association between accelerometer workload and injury risk has been found previously. However, any research has assessed the absorption dynamics of external workload through the measurement in different anatomical locations simultaneously. A cross-sectional study was designed to: (i) to describe the multi-joint external workload profile of youth soccer players, (ii) to identify differences between-participants related to anatomical locations, (iii) to analyze the workload dynamics at different speeds at joints and body segments, (iv) to characterize the multi-joint individual workload and the within-participants difference in each body segment. Twenty-one U-18 male players, that were part of a Youth Spanish First Division soccer team, performed an incremental running treadmill test and wore four WIMU PROTM inertial devices in lower limb (ankle-knee) and spine (lower-upper back) locations to register cumulative tri-axial accelerometry-based workload (PlayerLoad, PLRT). The main results have shown that the highest PLRT was detected at the lower limb, especially at the ankle. Different dynamics of accelerometer workload have been found between lower and upper limb, being them between ankle-knee at 12-km/h and lower-upper back at 9.5-km/h (p<.05). Between-participants` differences were shown at all joints, finding the highest differences at the upper back (p<.01; d=2.17). Finally, the body segment knee-lower back reported the highest differences (%diff=34.25-to-67.28; d=2.20-to-4.77). In conclusion, a great between-participants external workload variability was found at joints and body segments, being recommended for an individualized assessment and specific training protocols.